Raising the bar: Increasing protection for athletes in the Olympic movement from sexual harassment and abuse - Burke, A. M. (Journal of Legal Aspects of Sport, 2021)
After the Larry Nassar and USA Gymnastics scandal surfaced in 2016, the United States enacted a federal act titled "Protecting Victims from Sexual Abuse and Safe Sport Authorization Act of 2017." This Act requires immediate mandatory reporting to the U.S. Center for SafeSport for any alleged child abuse of an amateur athlete who is a minor. An increasing amount of legislation is being passed to address sexual harassment and abuse in sports in the United States; however, the International Olympic Committee (IOC), which governs the Olympic Movement, is lacking in its sexual harassment and abuse policies. This article will address how the IOC`s sexual harassment and abuse policies are not as robust as they should be. The amount of attention that the Olympics receives worldwide gives the IOC a global platform to be a leader in taking a stance on sexual harassment and abuse policies.